Essays on the influence of natural disasters and extreme weather on households' resilience and land management - Gharib, Mariam Hamed (My University, 2026)
Extreme weather events have increased in frequency and severity, and it is anticipated that these events will continue to rise into the future. These extreme weather events have affected the natural system, disrupting wildlife and ecosystem services, amongst other challenges. In order to mitigate the impacts of extreme weather events, individuals, households, and firms may need to adjust their behavior and way of life. In this study, we focus on the influence of these extreme weather events on households’ resilience and land management with respect to infrastructure services, conservation and preparedness, with a more concentrated focus on wildfire events. The focus on wildfire events stems from the frequency and intensity of these events and how they have been increasing, especially in the Great Plains of the U.S. We examined how wildfire influences natural systems in the first chapter. In the other two chapters, we look at how individual behavior is shaped by exposure to severe weather events in general. In chapter 1, we study the effect of wildfire and severe drought on Conservation Reserve Program (CRP) persistence. We define CRP persistence as the number of years in which grassland was the majority of the land use in an expired CRP contract parcel. In the literature, there is a lot of research on what influences CRP persistence, but little literature extensively examines the effects of wildfires and drought, as well as surrounding land use, on CRP persistence. To study this, we built a 10-year unique geodatabase at the CRP parcel level and used a Mixed Effects Weibull accelerated failure time model (AFTM) to do the analysis. We find that CRP persistence is 3 years on average. CRP persistence is higher if an expired CRP parcel or surrounding land is burnt by a megafire, located in mid-range drought, and increases for every increase in the percentage of grassland and open water for a 50m buffer and decreases if bordered by crops or found in more wet areas. There is a need for policy intervention through education to encourage landowners to retain CRP-based practices and enhance wildfire mitigation land management efforts on both CRP and post-CRP lands. Alternatively, the government can increase the likelihood of reenrollment for CRP lands classified as risky areas, such as those that are less connected or surrounded by crop production and located in wetlands or areas with higher rainfall. Chapter 2 estimates how much households are willing to pay (WTP) to avoid power outages that vary both in frequency and duration across states in the Great Plains of the U.S. because of severe weather events or natural disasters. A secondary objective was to assess the differences in WTP across different population segments, i.e. Metropolitan Statistical Areas and Non-Metropolitan Statistical Areas. With an ageing electric grid and power infrastructure that is more than 100 years old, power outages caused by severe weather events are more frequent and longer in duration, and the situation is expected to worsen in the future. Before building grid resilience and adopting different resilience technologies, we need to understand households’ WTP for such technologies in the case of a severe weather outage. Using primary data from a two-stage choice experiment and a theoretically consistent framework, we find that WTP was much higher when both duration and frequency varied, but this depended on the acceptable level of duration and frequency of power outage for a household. When comparing the WTP across MSA and N-MSA, we find that it is higher for the former. The positive WTP values show that a market exists for backup services, and utility companies, government, and community members can invest in the improvement of power infrastructure reliability and resilience, depending on the cost of investment and use the WTP values for resource planning and pricing. In my last chapter, Chapter 3, we examine the influence of alternative information sources on a household’s perceived level of wildfire and disaster preparedness and perceived confidence in being prepared for a wildfire or disaster between households in states in the Great Plains (GP) and mountainous western regions (MW) of the U.S. In the literature, understanding the effect of various disaster preparedness information channels across various geographical areas that differ in disaster preparedness resources is sparse. To do this, we analyze 3 years of an annual household disaster preparedness survey conducted by the Federal Emergency Management Agency, focusing specifically on households surveyed about wildfires. We find that the perceived level of wildfire and disaster preparedness or perceived confidence level to prepare for a wildfire or disaster does not differ between the two regions, and the effect of information sources on both is region-specific. Public announcements served as the strongest information source influencing disaster preparedness in the MW, while network sources served as the most influential information source for the GP. For the perceived confidence level to prepare for a wildfire and disaster, networks served as the strongest source, but the effect was mostly driven by MW. Practical implications suggest targeting more than one appropriate area-specific communication channel in each region for disseminating wildfire disaster preparedness information, as well as providing needed resources that ensure effective and efficient distribution of disaster preparedness information.
Keywords: Natural disasters; CRP persistence; Power outages; Wildfire preparedness; Information sources